2013
DOI: 10.3347/kjp.2013.51.3.327
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Molecular Cloning of a Protective Antigen from the Midgut of Haemaphysalis longicornis

Abstract: Vaccination is considered a promising alternative for controlling tick infestations. Haemaphysalis longicornis midgut proteins separated by SDS-PAGE and transferred to polyvinylidene difluoride (PVDF) membrane were screened for protective value against bites. The western blot demonstrated the immunogenicity of 92 kDa protein (P92). The analysis of the P92 amino acid sequence by LC-MS/MS indicated that it was a H. longicornis paramyosin (Hl-Pmy). The full lenghth cDNA of Hl-Pmy was obtained by rapid amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Moreover, immunization of female BALB/c mice with recombinant protein NP-M1-HSP60 induced immune responses, and protected mice from lethal influenza H7N9 virus challenge and significantly inhibited viral replication [ 22 ]. In our previous studies [ 7 ], 66 kDa proteins from H. longicornis had immunogenic properties, which might be Hsp60 verified later by LC-MS/MS. We also found similar results in the experiments of screening antigenic proteins from D. silvarum .…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…Moreover, immunization of female BALB/c mice with recombinant protein NP-M1-HSP60 induced immune responses, and protected mice from lethal influenza H7N9 virus challenge and significantly inhibited viral replication [ 22 ]. In our previous studies [ 7 ], 66 kDa proteins from H. longicornis had immunogenic properties, which might be Hsp60 verified later by LC-MS/MS. We also found similar results in the experiments of screening antigenic proteins from D. silvarum .…”
mentioning
confidence: 77%
“…The results of tick infestation challenge showed that rHlFER2 could significantly reduce the body weight of ticks infested from the rHlFER2-immunized rabbit compared to those from the control rabbits. Through mass spectrometry, Kim et al [ 6 ] and Hu et al [ 7 ] identified calreticulin and paramyosin (Pmy) from H. longicornis , respectively. These scholars have been trying to screen more effective antigenic proteins in the preparation of anti-tick vaccines.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By virtue of its major antigenic properties, this protein has been used for the development of diagnostic assays for filarioids of medical concern such as Wuchereria bancrofti and Brugia malayi [ 27 , 32 , 33 ]. Many studies of the paramyosin protein, as a potential vaccine candidate, have focussed on platyhelminths [ 34 39 ], with fewer studies on nematodes [ 40 , 41 ] and ticks [ 42 ]. An immunomodulatory effect of this protein has also been identified, inhibiting components of the complement cascade [ 43 , 44 ], binding of immunoglobulins and collagen [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%